2020
DOI: 10.3389/fmars.2020.587500
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Science-Policy Gap – Toward Better Integration of Decision Support Tools in Coastal and Marine Policy Implementation

Abstract: Decision support tools (DSTs), like models, GIS-based planning tools and assessment tools, play an important role in incorporating scientific information into decision-making and facilitating policy implementation. In an interdisciplinary Baltic research group, we compiled 43 DSTs developed to support ecosystem-based management of the Baltic Sea and conducted a thorough review. Analyzed DSTs cover a wide variety of policy issues (e.g., eutrophication, biodiversity, human uses) and address environmental as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We continued this discussion during the in‐person workshop to (1) gain insight into how likely the advisory panel and their stakeholders would be to use DSTs and (2) follow recommendations that the DST should be co‐developed with end‐users (Schumacher et al. 2020). Primarily, the panel expressed that they would like a DST to show different nutrient load reduction scenarios and fish biomass as well as showing ecosystem “winners” and “losers” over long‐term nutrient reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We continued this discussion during the in‐person workshop to (1) gain insight into how likely the advisory panel and their stakeholders would be to use DSTs and (2) follow recommendations that the DST should be co‐developed with end‐users (Schumacher et al. 2020). Primarily, the panel expressed that they would like a DST to show different nutrient load reduction scenarios and fish biomass as well as showing ecosystem “winners” and “losers” over long‐term nutrient reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Responses indicated that the ecosystem model would be useful to compare with stock assessments, inform stock assessments, communicate results with agencies, advance ecosystem-based fisheries management, inform the Louisiana Nutrient Management Strategy, and inform strategic decision making. We continued this discussion during the in-person workshop to (1) gain insight into how likely the advisory panel and their stakeholders would be to use DSTs and (2) follow recommendations that the DST should be co-developed with end-users (Schumacher et al 2020). Primarily, the panel expressed that they would like a DST to show different nutrient load reduction scenarios and fish biomass as well as showing ecosystem "winners" and "losers" over long-term nutrient reduction.…”
Section: What Levels Of Uncertainty Are Acceptable To Management?mentioning
confidence: 99%
“…It is further emphasized that the ability to understand and manage such a complex socioecological system therefore requires a systems analysis approach which has a solid underpinning theoretical framework, but which is then able to be implemented by stakeholders (Elliott et al, 2020b). As such, a simplicity of implementation, flexibility, and transparency are key to this process, as it enhances acceptance by key stakeholders, especially as a decision support tool (Nygård et al, 2020;Schumacher et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Whether they are used in MSP depends on these tools being easily accessible, easily understandable, and not too resource demanding [16]. A comprehensive survey in the Baltic Sea region highlights the need among MSP practitioners for improved user guidelines and online training on how to use spatial DSTs [17]. With online tutorials and webinars, more users are likely to use the tools [18].…”
Section: Introductionmentioning
confidence: 99%
“…MYTILUS has been further extended during the BONUS BASMATI project to include various tools for scenario building in addition to CIA to support MSP processes. Pınarbaşı et al (2017) [15] argued how "education and training should be a prerequisite to introducing a DST into the MSP process" and that the "importance of educating and training non-technical users, including marine planners and stakeholders may be underestimated by DST developers and advocates", points supported by Schumacher et al (2020) [17] who recommended the development of "user-friendly guidelines" for end-users in public authorities regarding applying spatial DSTs. This research presents the systematic building stones of a new MYTILUS training set developed for a workshop in December 2021 in the Interreg BSR Capacity4MSP project and tested as part of an online PhD course in January 2022 in the ERASMUS+ project Knowledge Flows in MSP in active learning environments.…”
Section: Introductionmentioning
confidence: 99%